2006
DOI: 10.1108/09596110610658634
|View full text |Cite
|
Sign up to set email alerts
|

The use of management contracts by international hotel firms in Thailand

Abstract: Seeks to examine the extent to which management contracts used by international hotel firms in Thailand mirror those used in the USA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…For example, a recent study shows that, when well-established brands pursue international expansion through management contracts, their core competence related to their management expertise, such as human resources, may be influenced (Gannon et al, 2010). Panvisavas and Taylor's (2006) study also revealed that the practice of management contract was different in Thailand compared to in the USA. Consequently, it is reasonable to suspect that the effects of brand and/or operator on hotel financial performance may vary in different countries.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…For example, a recent study shows that, when well-established brands pursue international expansion through management contracts, their core competence related to their management expertise, such as human resources, may be influenced (Gannon et al, 2010). Panvisavas and Taylor's (2006) study also revealed that the practice of management contract was different in Thailand compared to in the USA. Consequently, it is reasonable to suspect that the effects of brand and/or operator on hotel financial performance may vary in different countries.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…More recent evidence suggests that the use of management contracts has risen further to 55 per cent in the United States (Smith Travel Research, 2003). Beals and Denton (2005), Panvisavas and Taylor (2006), and Corgel (2007) provide further recent testimony of management contracts’ increasing popularity.…”
Section: Management Contracts and The Ffande Reserve Literature Reviewmentioning
confidence: 98%
“…For example, in Thailand the hotel industry is regulated by the Alien Business Act of 1999. According to this Act, a foreign partner in an IJV is only permitted to contribute up to 49% of the total investment in the IJV (Panvisavas and Taylor, 2006). Hence, it is not possible for the foreign parent to have equal or majority ownership in a hotel joint venture in Thailand.…”
Section: Fostering the Flow Of Knowledge At An Organization-wide Levelmentioning
confidence: 98%